Genome sequence survey of local isolated alkaliphilic bacillus sp. GI - Liew, Chong Wai; Md. Illias, Rosli; Hassan, Osman; Mahadi, Nor Muhammad; Najimuddin, Nazalan (2005)
Bacillus sp. GI is an alkaliphilic microorganism which cannot grow or grow poorly under neutral pH conditions, but grow very well at pH higher than 9.5. Since 1969, a great number of alkaliphilic Bacillus strains from various environments were isolated and a variety of alkaline enzymes were obtained and successfully purified. Therefore, Genome Sequence Survey (GSS), an efficient procedure for gene discovery and genome characterization was used to discover novel functional gene and applicable industrial enzyme. GSS was carried out by determining and publicly distributing 300 –1000bp of single-pass nucleotide sequence from both ends of thousands of randomly genomic-DNA clones. In total, approximately 400,000 nucleotides (613 sequence tags) of non-redundant, high-quality Bacillus sp GI genome sequence were obtained. Sequence tags were searched against the GBBCT (Genbank Bacterial Sequences), Bacillus subtilis and Bacillus halodurans databases. Results showed that, Bacillus sp. GI possessed a few useful and applicable industrial enzymes, such as protease, lipase, xylanase, glucanases and CGTase. Besides, a gene encoded for Na+/H+ antiporter membrane protein, a major or component in alkaliphile Na+ cycle, was also found in the Bacillus sp. G1 genome. The Na+/H+ antiporter activity plays an important role in pH homeostasis and maintaining low intracellular sodium concentrations in halophilic or halotolerant aerobic bacteria. This explained how this microorganism is able to survive in this harsh environment. Other major components in alkaliphile Na+ cycle, such as Na+/solute symporter, flagella, ABC transporters, and Teichuronopeptide (TUP), were also found in Bacillus sp. G1.